Daya Terima dan Nilai Gizi Bolu Kukus Substitusi dari Tepung Terigu dan Tepung Kacang Hijau Sangrai - Vifiyanti, Widya; Chandra, Filius; Kawuri Putri , Satiti (Prosiding Seminar Kesehatan Nasional, 2024)
Mung beans are generally only processed into mung bean porridge or filling in snacks such as onde-onde and bakpia. However, mung beans can be processed into flour which is used as an ingredient in processed steamed biscuit products. Therefore, there is a need to develop steamed sponge products using local food ingredients that are readily available at affordable prices but have full nutritional value, especially protein and water content and low gluten content compared to steamed sponge in general. The aim of this study was to determine the effect of replacing wheat flour with roasted mung bean flour on the acceptability, moisture content and protein content of steamed sponge. This research is an experimental study using a completely randomised design (CRD) with 4 treatments of steamed sponge cake substituted by wheat flour and roasted mung bean flour. The organoleptic test was carried out by 30 untrained panelists, then the organoleptic test results were analysed using SPSS one-way ANOVA and Tukey's post hoc test. This study shows that the acceptability and nutritional value of the steamed sponge cake substituted by wheat flour and roasted mung bean flour obtain the best average value preferred by the panelists, namely in sample P2 (75% wheat flour: 25% roasted mung bean flour) both in terms of colour 4.07 (like), aroma 3.63 (rather like), texture 4.10 (like) and taste 3.94 (rather like). From the results of this study it can be concluded that the substitution of wheat flour and roasted mung bean flour has a significant effect on the acceptability of the texture parameters of steamed sponge cake and has no significant effect on the aroma, colour and taste of steamed sponge cake. The P2 treatment (75% wheat flour: 25% roasted mung bean flour) is the best formulation treatment, while the nutritional value of the steamed sponge cake is not affected.